Potential for Development of Bukuran Cluster Museum as Educational Tourism in Bukuran Village, Sragen, Center Java - Lesty, Merby Ariana; Sabardilla, Atiqa (PAEDAGOGIA, 2023)
This article discusses the Bukur Cluster Museum, which was built to showcase the various fossils discovered by the people of Bukur Village. The aim of the museum is to provide community members with an appreciation for the vital discoveries made in their area. The research method used to study the museum is qualitative, which involved observing the museum and conducting interviews with museum administrators. The Bukur Cluster Museum provides visitors with various theories of evolution and factors related to human development in the past. The museum's exhibits are comprehensive, displaying a wide range of fossils and other artifacts, which showcase the history of human development in the area. The Bukur Cluster Museum has significant potential as an educational tourist attraction due to its completeness and relevance to human history. Visitors can learn about the history of human development in Bukur Village and how the fossils were discovered. Overall, the Bukur Cluster Museum serves as a testament to the importance of preserving historical artifacts and educating people about the past. It also shows the value of local community involvement in preserving their history and cultural heritage.